Management and Operation of the E-Government (African Journal of Public Administration & Management, 2026)
e-Government Authority (e-GA) is a public institution established by eGovt Act 2019. Before it operated without special act resulting in limitations on enforcement. It is mandated to coordinate, oversee, promote e-Government initiatives and enforce e-Government related policies, laws, regulations, standards and guidelines in public institutions in order to improve Government efficiency and service delivery to the general public through ICT.
Keywords: Management; E-Government; Operation of the E-Government